2006
DOI: 10.1126/science.1129116
|View full text |Cite
|
Sign up to set email alerts
|

Wetland Sedimentation from Hurricanes Katrina and Rita

Abstract: More than 131 x 10(6) metric tons (MT) of inorganic sediments accumulated in coastal wetlands when Hurricanes Katrina and Rita crossed the Louisiana coast in 2005, plus another 281 x 10(6) MT when accumulation was prorated for open water area. The annualized combined amount of inorganic sediments per hurricane equals (i) 12% of the Mississippi River's suspended load, (ii) 5.5 times the inorganic load delivered by overbank flooding before flood protection levees were constructed, and (iii) 227 times the amount … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
180
2
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 291 publications
(193 citation statements)
references
References 7 publications
10
180
2
1
Order By: Relevance
“…The δ 13 C maximum at the same depth also indicates a more significant contribution for OC from C4 plants during the 1950's to early 1960's, coincident with the times of major hydrological changes both in the upper and lower reaches of the Mississippi River drainage basin. Most recently, hurricanes Rita and Katrina allowed a study of their effects on wetlands in Lousiana (Turner et al, 2006), which concluded that hurricanes nourish rather than erode wetlands. Recent sediments in our core contain younger (1560 years) and isotopically lighter OC (-21.96 ‰), suggesting a lesser influence of wetland carbon deposits, in accordance with the increased channelization of the Mississippi and Atchafalaya Rivers in recent times.…”
Section: Discussionmentioning
confidence: 99%
“…The δ 13 C maximum at the same depth also indicates a more significant contribution for OC from C4 plants during the 1950's to early 1960's, coincident with the times of major hydrological changes both in the upper and lower reaches of the Mississippi River drainage basin. Most recently, hurricanes Rita and Katrina allowed a study of their effects on wetlands in Lousiana (Turner et al, 2006), which concluded that hurricanes nourish rather than erode wetlands. Recent sediments in our core contain younger (1560 years) and isotopically lighter OC (-21.96 ‰), suggesting a lesser influence of wetland carbon deposits, in accordance with the increased channelization of the Mississippi and Atchafalaya Rivers in recent times.…”
Section: Discussionmentioning
confidence: 99%
“…Accretion of over 3 cm was measured throughout the southern Louisiana coast from recent hurricanes Katrina and Rita [38]. Sediment deposition from hurricanes Katrina, Rita, Gustav, and Ike totaled 68, 49, 21, and 33 million metric tons, leading to maximum accretion rates of 21, 20, 7, and 17 g/cm 2 , respectively [19].…”
Section: The Role Of Hurricanes As "Land-builders" For Coastal Louisianamentioning
confidence: 99%
“…Tidal energy appeared to be driving the magnitude of the flux within the tidal channels in these salt marshes. In other marshes, storm-driven surge has accounted for a large percent of sediment fluxes over time (Cahoon et al 1996;Turner et al 2006;Fagherazzi et al 2013b). However, not all of our sites responded to tidal energy; the discrepancy is likely a result of the lower range of velocities observed in Seal Beach2.…”
Section: Discussion Atmospheric and Tidal Controls On Sediment Transportmentioning
confidence: 99%